Explore the Monitoring Status of Black and Odorous Water - Wang Zhihao (MATEC Web of Conferences)
Black and odorous water bodies caused by industrial pollution, agricultural runoff and urban wastewater pose environmental and public health risks. Traditional monitoring methods are both time and labour consuming limitations, which is unsuitable for large-scale assessments. Remote sensing has emerged as a new monitoring technology using spectral analysis and machine learning techniques to detect polluted water bodies with accuracy of 87.5%. This study examines the formation mechanisms of black-odorous water based on odorzing and blackening process. It also compares advantages and limitations of both traditional monitoring techniques and modern remote sensing methods. Challenges on remote sensing monitoring including atmospheric effect and ground effect decrease its accuracy, but future advancements in high-resolution satellite imaging, cloud-masking techniques and next generation machine learning model have potential to overcome those challenges. Stricter pollution regulations are also necessary to enhance water quality management. Strengthening these efforts is essential for sustainable urban development and environmental protection.